Absolute pitch: Common traits in music and language - RAKOWSKI, Andrzej; MIYAZAKI, Ken'ichi (Archives of Acoustics, 2007)
Absolute pitch in music means an ability of long-term auditory memory to store pitch standards corresponding to within-octave musical pitch classes, based on a generally recognized reference pitch. Such an ability, extremely rare among Western musicians, appears much more commonly among musicians of Asiatic countries. Hypothetically, it is due to either the special forms and early beginnings of musical education (Japan), or to a sort of "preconditioning" of the pitch-memory system in infants and very young children, to treat pitch value as a meaningful element of speech communication (countries with tone languages). Similarities and differences between absolute pitch in music and the memory for pitch value in tone languages will be discussed in detail.